Capital Structure and Financial Performance on Company Value with Profitability as an Intervening Variable - Rima, Rima; Lusiana, Lusiana; Sari, Desi Permata (GOVERNORS, 2025)
This study aims to determine the influence of capital structure and financial performance on company value with profitability as an intervening variable in primary sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The type of data used is quantitative data and the analysis used is multiple linear regression analysis and path analysis. The data was processed using SPSS 26. Based on the results of hypothesis; Partial capital structure does not have a significant effect on profitability.; Partial financial performance has a significant effect on profitability; Partial capital stucture has a significant effect on firm value; Partial financial performance has a significant effect on firm value; Partial profitability does not have a significant effect on firm value; Profitability as an intervening variable cannot mediate between capital structure and firm value; Profitability as an intervening variable cannot mediate between financial  performance and firm value. It is hoped that this study can help manufacturing companies listed on the Indonesia Stock Exchange (IDX) to increase the value of the company by considering factors that have a significant effect on the value of the company such as capital structure and financial performance.